IMPLEMENTATION OF SOLAR ENERGY IN AGRICULTURE: REVIEW - et. al., Dr Archana (International Journal of Modern Agriculture, 2021)
Country like India have some locations where solar radiation is very high which is waste as it falls on the ground. It has been estimated that if 1% of the received solar radiations can be converted to energy then this energy can meet the energy crisis of the future world. Not only in solar radiations but India also have a vast sector of agriculture that fill the stomach of major world population. Indian government have applied some policies to increase the use of solar energy to decrease the use of non-renewable resources. Current study discusses the various advancements in the utilization of solar energy in the agriculture of India that can be used to decrease the power consumption from non-conventional sources which are costly as well as not environmentally friendly. It has been concluded from current research that there is still further research is required to increase the application and efficiency of utilization of the solar power for its sustainable utilization.